Online Learning Objects in higher education, an alternative in times of pandemic - Jenniffer Sobeida Moreira Choez, Letty Araceli Delgado Cedeño, María Elena Mendoza Vélez, María Patricia Delgado Cedeño, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research was to describe the benefits of Online Learning Objects as didactic strategies for teaching and learning in higher education in times of pandemic. The methodology used was based on the qualitative paradigm, applying the deductive method; the type of research was descriptive bibliographic documentary, through content analysis of scientific articles and research papers as the basis of the study. The analysis of the results was carried out through content analysis according to categories of research interest. It was possible to establish several advantages and benefits associated with the use of Online Learning Objects to improve the teaching-learning process in different areas of higher education, especially in times of pandemic.